OS 24-04 A PILOT STUDY ASSESSING THE FEASIBILITY OF VASCULAR FUNCTION IN LOW SOCIOECONOMIC STATUS PRESCHOOL CHILDREN. (September 2016) - Ghazi, Lama; Dudenbostel, Tanja; Ejem, Deborah; Turner-Henson, Anne; Joiner, Cynthia Irwin; Affuso, Olivia; Azuero, Andres; Calhoun, David A.; Rice, Marti; Hage, Fadi; Oparil, Suzanne
Abstract : Objective: To assess the feasibility of measuring non-invasively central aortic blood pressure (BP) and indices of arterial stiffness (aortic augmentation index (AIx) and pulse wave velocity (PWV)) in 3–5 year old children and assess if vascular function is affected by vascular inflammation (Serum C-reactive protein (CRP)) and /or cortisol. Design and Method: Central BP, AIx, and PWV were measured using applanation tonometry (SphygmoCor) in 16 children recruited from Head Start centers in AL. Results: We recruited 16 preschool African American children (age 53.1 ± 9.1 months, 69% males, weight 39.8 ± 8 lbs, height 36.2 ± 3.2 in). Of these 38% (n = 6) had an elevated blood pressure reading (> 90% for height, gender and age). BMI were comparable between the groups. Brachial (111 ± 9/69 ± 4 vs. 93 ± 11/55 ± 6 mmHg, p < 0.05) and central (93 ± 12/72 ± 6 vs. 85 ± 7/57 ± 6 mmHg, p < 0.05) BP, CRP (3.1[2.3–6.3] vs. 0.2[0.1–0.3] mg/L, p < 0.05) and cortisol (0.21 ± 0.09 vs. 0.15 ± 0.06, p = 0.09) were higher in children with hypertensive BP readings. There was no significant difference in PWV between the groups but AIx was higher in children with hypertensive BP readings (31 ± 8 vs.18 ± 16%, p = 0.07). Serum CRP correlated with systolic (Spearman r = 0.70) and diastolic (0.68) BP percentiles and with central systolic (0.58) and diastolic (0.71) BP readings (all p < 0.05) but not with AIx (0.25, p = 0.4) or PWV (−0.2, p > 0.9). Serum cortisol showed moderate correlations with AIx (0.43, p = 0.1) and PWV (-0.48, p = 0.1) but not with BP readings. Conclusions: Non-invasive assessment of central aortic BP and measures of arterial stiffness are feasible in preschool children. Children with hypertensive BP readings may have evidence of arterial stiffness as early as 3–5 years of age. Vascular function is associated with inflammatory and stress markers. Further studies are needed to determine vascular function changes in preschool children to elucidate mechanisms of early onset hypertension.